Cover Picture: Tunable Thermoelastic Anisotropy in Hybrid Bragg Stacks with Extreme Polymer Confinement (Angew. Chem. Int. Ed. 3/2020). Issue 3 (12th December 2019) - Wang, Zuyuan; Rolle, Konrad; Schilling, Theresa; Hummel, Patrick; Philipp, Alexandra; Kopera, Bernd A. F.; Lechner, Anna M.; Retsch, Markus; Breu, Josef; Fytas, George
Abstract : Hybrid Bragg stacks consisting of alternating clay nanosheets and extremely confined polymers are fabricated by a scalable spray‐coating process. In their Research Article on page 1286, M. Retsch, J. Breu, G. Fytas et al. show that an unprecedented cross‐plane periodicity and tunable confinement down to Angstrom precision can be achieved. The resulting anisotropic thermoelastic properties demonstrate remarkable ratios of in‐plane to cross‐plane thermal conductivity up to 38 and corresponding Young′s moduli up to 7.